Media Poster dengan Pendekatan Etnosains: Pengembangan Bahan Ajar IPA Siswa Sekolah Dasar - Ida Fiteriani; Nadia Kurnia Ningsih; Irwandani Irwandani*; Kurnia Santi; Romlah Romlah (Jurnal Pendidikan Sains Indonesia, 2021)
This research is based on the need for the importance of a learning media that can introduce local wisdom dan national culture. The research method uses the ADDIE model with 5 stages; Analysis, Design, Development, Implementation, dan Evaluation. In the needs analysis stage, the fact is that there are still not many learning media that contain local wisdom (ethnoscience). The results of the analysis are then continued with the stage of designing an ethnoscience learning media that is in accordance with the characteristics of fourth grade students in elementary schools dan madrasah ibtidaiyah. Poster media was chosen as the media to be developed in this research. This media is then designed in such a way as to combine the concept of science learning with the value of local wisdom in the province of Lampung. The data collection technique used a material expert questionnaire, media expert, linguist, educator response questionnaire dan student response questionnaire. The poster media design was then validated by 6 experts. Based on the final validation results, the percentage of assessment was 89.3% from media experts, 93.3% from material experts dan 91% from linguists with "very feasible" criteria based on the interpretation criteria of the validation results. The next stage is then testing the learning media products on users. The trial was conducted on 35 students in two schools, namely elementary school dan madrasah ibtidaiyah. Based on the results of the questionnaire, the percentage of satisfaction was 91%. The results of the questionnaire were combined with observations dan interviews which described the same results. Based on the results of the assessment, it can be concluded that the poster learning media is very feasible to be used as a science learning medium in SD dan MI. The results of this study are expected to be used as a reference for teachers in developing poster learning media containing ethnoscience.